SAIR reconstruction method based on deep generalized unfolding network - Xiaocheng Yang; Zihan Hou; Weihao Cheng; Jingye Yan; Lin Wu; Mingfeng Jiang; Bo Wei (Advances in Space Research, 2026)

Comprehensive cooling strategy for long-distance blind-heading tunnel construction in tropical plateau regions: a case study - Zhu Peng; Chenghua Shi; Chaojun Jia; Yingzhe Jiang; Hong He; Keyue Zheng; Mingfeng Lei (Tunnelling and Underground Space Technology, 2026)

Comparative analysis of fully-coupled towing simulation for a 15MW floating wind turbine using FAST2AQWA method - Mingsheng Chen; Suqian Liu; Xingyu Jiang; Mingfeng Hu; Zhuo Li; Jiale Jiang; Junyu Li (Ocean Engineering, 2026)

In situ therapeutic vaccine gel induces pyroptosis and remodels tumor microenvironment to prevent postoperative hepatocellular carcinoma recurrence and metastasis - Liangdi Jiang; Faisal Raza; Shiqi Yang; Kunwei Li; Hang Xiao; Wenjing Chen; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2026)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Metabolic profiling of triptophenolide in rat plasma, urine, bile and faeces after intragastric administration - Mingfeng Jiang; Qiang Hou; Shuilian Wu; Xiaofan He; Tingting Zhang; Rongjing Zhou (Natural Product Research, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Optimal planting density enhances cotton yield by coordinating boll–leaf system photosynthesis under heat-limited conditions - Minzhi Chen; Yinhua Yan; Peng Yan; Yali Zhang; Jingshan Tian; Mingfeng Yang; Chuangdao Jiang; Wangfeng Zhang (Field Crops Research, 2025)

Combined techniques for antigen-specific nanobody discovery in the white-spotted bamboo shark (Chiloscyllium plagiosum) - Bo Zhong; Junjie Yang; Kaixi Zheng; Wenjie Tang; Lei Jia; Mingfeng Gu; Jinming Hu; Xiaofeng Jiang; Jianqing Chen; Zhengbing Lyu; Guodong Chen (Fish & Shellfish Immunology, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Climate change induced environmental variability affects the tuna catch composition: a perspective of catch mean trophic level - Mingfeng Jiang; Jintao Wang; Xinjun Chen (Acta Oceanologica Sinica, 2025)

A leader-adaptive particle swarm optimization with dimensionality reduction strategy for feature selection - Shanshan Yang; Bo Wei; Li Deng; Xiao Jin; Mingfeng Jiang; Yanrong Huang; Feng Wang (Swarm and Evolutionary Computation, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

SP94 engineered erythrocyte membrane enhanced the targeted delivery of biomimetic nanosuspension with IDO immunotherapy and chemotherapy in liver cancer - Faisal Raza; Liangdi Jiang; Shulei Zhang; Hajra Zafar; Yujiao Qiu; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2024)

Formula model established through field application of glass slides and rapid analysis of pesticide residues in vegetables by ion mobility spectrometry - Yong Mei; Mingfeng Huang; Wayne Jiang; Gaoqing Yuan; Xuesheng Li (Food Control, 2024)

Is seasonal closure an effective way to conserve oceanic squids—Taking Chinese autonomic seasonal closure on the high seas as an example - Mingfeng Jiang; Jintao Wang; Gang Li; Bilin Liu; Xinjun Chen (Fisheries Research, 2024)

What happened in COVID to conflict: Re-examination of financial inclusion and green development nexus in China natural resource sector - Chen She; Mingfeng Jiang; Jianhua Du; Jiaxiang Xu; Xincheng Zhu (Resources Policy, 2023)

CYP2C9 inhibits the invasion and migration of esophageal squamous cell carcinoma via downregulation of HDAC - Zhenzhen Jiang; Xiaoli Zheng; Weijia Wang; Liqing Qiu; Lingrong Yang; Mingfeng Jiang; Yuhui Hua (Molecular and Cellular Biochemistry, 2021)

Improved robust tensor principal component analysis for accelerating dynamic MR imaging reconstruction - Mingfeng Jiang; Qiannan Shen; Yang Li; Xiaocheng Yang; Jucheng Zhang; Yaming Wang; Ling Xia (Medical & Biological Engineering & Computing, 2020)

First report of summer canker caused by Pectobacterium carotovorum subsp. actinidiae on kiwifruit in Jiangxi, eastern China - MingFeng Yan; Bing Liu; ManFei Zou; Ying Zhou; JunXi Jiang (Journal of Plant Pathology, 2019)

Major Energy Plants and Their Potential for Bioenergy Development in China - Xiaofeng Li; Shenglin Hou; Man Su; Mingfeng Yang; Shihua Shen; Gaoming Jiang; Dongmei Qi; Shuangyan Chen; Gongshe Liu (Environmental Management, 2010)